Does the growth of the digital economy boost the efficiency of synergistic carbon-haze governance? evidence from China - Zhou, Bin; Zhao, Haoxiang; Yu, Jingyue; He, Taiyi; Liu, Jiawei (Frontiers in Environmental Science, 2022)
As global urbanization continues to accelerate, so does the amount of harm to the natural ecological environment caused by excessive resource extraction. In several Chinese cities, haze and excessive greenhouse gas emissions have become crucial to the development of an ecological society. To break the previous energy-intensive development model, the data element has emerged as a key driver of the new cycle of high-quality development. Therefore, additional investigation into the synergistic influence of the digital economy as a new factor on air pollution and CO2 emissions is warranted. This study examines the effects, spatial effects, and transmission mechanisms of the digital economy on the synergistic control of carbon and haze using panel data from 30 provinces in China from 2013 to 2019. The study concludes that the digital economy has an overall significant inhibiting effect on carbon dioxide emissions and haze pollution levels (the regression coefficients are -1.090 and -0.714 respectively), a significant driving effect on the efficiency of synergistic carbon and haze management, a spatial spillover effect, and a positive effect on neighboring regions (the regression coefficient is more than 0.239). By region, the digital economy in the eastern region has a greater impact on the effectiveness of carbon and haze management, whereas the digital economy in the western region has a greater impact on CO2 emission reduction, and the digital economy in the central region has an effect that is more consistent with the overall situation. Moreover, the digital economy may successfully encourage technical innovation, which in turn supports synergistic carbon and haze governance, and technological innovation plays a very important mediating role in this transmission mechanism, a finding that is resilient to geographical interaction effects. Consequently, relevant policy recommendations are presented.